Model-based design of dynamic firing patterns for supervisory control of diesel engine vibration - Gosala, Dheeraj B.; Raghukumar, Harikrishnan; Allen, Cody M.; Shaver, Gregory M.; McCarthy, James E.; Lutz, Timothy P. (Control engineering practice, 2021)
Diesel engine cylinder deactivation (CDA) has been demonstrated to provide significant efficiency and aftertreatment thermal management benefits, enabling fuel-efficient emissions reduction from modern diesel engines at low load engine operation. Dynamic cylinder activation (DCA), a variant of CDA where the set of deactivated cylinders varies on a cycle-by-cycle basis, has been demonstrated to enable greater control over driveline torsional vibration while maintaining the fuel efficiency and thermal management benefits shown by fixed CDA via appropriate design of firing patterns. A model-based algorithmic approach to designing firing patterns during DCA – to control driveline torsional vibration in a user-defined frequency range, given firing density, engine speed, and maximum length of firing pattern – is described in this article. The described algorithm is generalizable to any engine configuration including different piston–cylinder layouts and number of cylinders. The algorithm is extended to design firing patterns for constrained DCA operation when CDA hardware is installed on a subset of cylinders of the engine. The resulting optimal firing patterns using the algorithm, for various combinations of inputs, are presented through an experimentally-validated simulation framework and discussed. It is demonstrated that the weighted phase-angle approach can accurately predict the frequencies and relative amplitudes of the vibration content, and, if theoretically possible, the proposed algorithm determines firing patterns that meet the specified requirements. The presented algorithm can be easily extended in future work for simultaneous selection of firing density and firing pattern during online, real-time implementation during both steady-state and transient operating conditions. •Model-based algorithm is presented for designing firing sequences during dynamic cylinder activation (DCA).•Algorithm enables control of torsional vibration in an undesirable frequency range.•Phase-angle approach is used to identify and optimize vibration at a given frequency.•Results are demonstrated with several combinations of frequencies and firing densities.•Vibration control is possible even when only a subset of cylinders is capable of CDA.